Biomechanical comparison of a 3D-printed prosthetic foot with conventional feet in people with transtibial amputation: a prospective cohort study - Trinler, Ursula; Heitzmann, Daniel; Hitzeroth, Sebastian; Alimusaj, Merkur; Rehg, Mathias; Hogan, Aidan (Prosthetics and orthotics international, 2023)
Introduction: - The method of 3D printing is increasingly gaining utilization in clinical applications and may support prosthetic fitting. The aim was to compare biomechanical outcomes of people with a transtibial amputation using a novel, individualizable, 3D-printed prosthetic foot (ComfyStep, Mecuris) with two conventional, widely used prosthetic feet during level ground walking using a 3D motion analysis system. - Methods: - Ten individuals with an unilateral transtibial amputation were fitted with 3 prosthetic feet (ComfyStep, Assure/Össur, DynamicMotion/Ottobock) using their current, well-fitting socket. They had at least 1 week of familiarization for each foot before gait analyses were conducted. Kinematics and kinetics as well as roll over shape (ROS) length and radius were calculated and compared between feet. - Results: - The sound side gait parameters of the participants were comparable when using different feet. However, there were differences on the affected side. The statistical analysis revealed that the 3D-printed foot differed significantly compared with the conventional feet in the following aspects: reduced range of motion, increased plantar flexion moment, reduced plantar flexion power, larger ROS radius, less favorable energy ratio, and higher overall stiffness. - Conclusion: - In principle, 3D-printed feet have advantages over conventional “off the shelf” feet, as their biomechanical characteristics could be adjusted more in detail according to the patient needs. Although, differences between conventional feet and the ComfyStep were shown. Whether these differences have a negative clinically relevant effect remains unclear. However, results suggest that commercially available 3D-printed feet should incorporate systematically better adjustments, for example, for stiffness, to enhance prosthetic performance.
Gesehen am 22.02.2024